The Current State of Research on the History of Christianity in China in Korean Academic Circles - LI, Huiyuan (Journal of Research for Christianity in China (JRCC), 2023)
PrefaceStudies on Nestorianism and the Yelü-Kewen ReligionStudies on the History of CatholicismStudies on the History of ProtestantismHistory of Sino-Korean Relations